2022
DOI: 10.1155/2022/4555490
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine and Other Sulfur-Donors as a Preventative and Adjunct Therapy for COVID-19

Abstract: The airway epithelial glycocalyx plays an important role in preventing severe acute respiratory syndrome coronavirus 2 entry into the epithelial cells, while the endothelial glycocalyx contributes to vascular permeability and tone, as well as modulating immune, inflammatory, and coagulation responses. With ample evidence in the scientific literature that coronavirus disease 2019 (COVID-19) is related to epithelial and endothelial dysfunction, preserving the glycocalyx should be the main focus of any COVID-19 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 236 publications
(742 reference statements)
2
15
0
Order By: Relevance
“…Similarly, the study conducted by Taher et al supports the bene cial effect of NAC in treating Covid-19 patients [19]. Moreover, the investigation conducted by Du Preez HN et al produced results consistent with our study, demonstrating positive outcomes with the use of NAC [20]. Although these studies provide encouraging ndings, it is important to continue exploring and validating the e cacy of NAC as a treatment for Covid-19.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, the study conducted by Taher et al supports the bene cial effect of NAC in treating Covid-19 patients [19]. Moreover, the investigation conducted by Du Preez HN et al produced results consistent with our study, demonstrating positive outcomes with the use of NAC [20]. Although these studies provide encouraging ndings, it is important to continue exploring and validating the e cacy of NAC as a treatment for Covid-19.…”
Section: Discussionsupporting
confidence: 89%
“…A recent review has posited that N-acetylcysteine supplementation is a potential tool against SARS-CoV-2 and may suppress viral replication [24]. However, clinical trials demonstrating its potential benefits have yet to be evidenced, but several studies have posited that its use alone, in various doses or in combination with other antiviral agents or vitamins (i.e., vitamin D) can dramatically reduce the rate of hospitalization, mechanical ventilation, and mortality [23][24][25]. In view of this growing interest, interestingly our results have shown that there is an improvement in symptoms and physical well-being following its adjunctive use in the management of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…P.O. ), (100 mg/kg/day IV), and multiple organ failure (150 mg/kg/day IV) [24]. Currently, there are no studies from reliable sources that reveal the exact dosage of the supplement Inmunocal®, neither for patients with COVID-19 nor for the general population; however, there are images and information from consultants of this product recommending the use of two sachets in healthy patients and four or more in patients with a chronic disease (i.e., patients with mild pain can consume 20 grams of Inmunocal® and in severe cases, the dosage could be increased to 30 grams) [26].…”
Section: Discussionmentioning
confidence: 99%
“…In order to supplement the restoration of the dysfunctional, attenuated, or loss of the ecGCx as occurs in sepsis, COVID-19, neuroinflammation and neurodegenerative disease, and T2DM, one would need to make provisions for an adequate supply of sulfur compounds and/or thiols [ 151 ]. From this standpoint, sulodexide (SDX), a heparin sulfate-like compound resistant to degradation by heparanase, accelerated ecGCx regeneration in vitro and in vivo [ 169 ], sodium thiosulfate (STS) [ 136 , 170 ], and n-acetyl-cysteine (NAC) [ 171 ] are approved and available for clinical use and have been recently utilized in the treatment of the T2DM and sepsis, glia-mediated neuroinflammation in neurodegenerative disease, and COVID-19.…”
Section: Mets Reloaded and Endothelial Activation (Ec Act ...mentioning
confidence: 99%